The association between character strengths and job crafting among nurses in tertiary hospitals: A cross‐sectional survey - Minli Li; Huimin Sun; Junhui Zhou (Wiley, 2023)
Abstract Aim This study was to investigate the association between character strengths and job crafting among nurses in tertiary hospitals in China. Design A cross‐sectional survey was conducted. Methods From February 2021 to April 2021, 1006 nurses from four tertiary hospitals in China were recruited to complete a series of online questionnaires assessing their job crafting and character strengths. The analysis was conducted using structural equation modelling (SEM). Results The mean scores for task crafting, cognitive crafting and relationship crafting were 3.19 ± 0.58, 3.50 ± 0.55 and 3.58 ± 0.51. There is a moderate level of job crafting and character strengths among Chinese nurses working at tertiary hospitals. Additionally, it was revealed by the SEM that character strengths contributed to 81% of the variance of job crafting and job crafting was positively correlated with nurses' character strengths. The study shows the need to develop nurses' character strengths to enhance job crafting behaviours.